Designing Business Process Model and Standard Operating Procedures (SOP) of Integrated Laboratory Management At XYZ University - Amalia Ika Nur Fauziati Abdullah; Lovinta Happy Atrinawati; Yuyun Tri Wiranti (Universitas Ahmad Dahlan, 2022)
Business processes and Standard Operating Procedures (SOP) are an integral part of organizations as a guideline to do activities to achieve their objectives. However, the integrated laboratory, established in 2020 as one of XYZ University’s facilities to support learning and research activities, does not have an SOP yet. Thus, this study aims to design and develop business process models and SOP documents of integrated laboratory management as instructed in the Regulation of Minister of Research, Technology, and Higher Education Number 71 of 2017. The information regarding the business process was gathered by analyzing other laboratories’ SOP and interviewing stakeholders. The interviewees were the Head of Integrated Laboratory Center of XYZ and the Head and Secretary of LPPM. After being developed, the business process models and SOP were presented to and approved by the process owner. These study outcomes are 25 business process models and 25 SOP documents of integrated laboratory management that have been verified by the Head of the Integrated Laboratory Center of University XYZ. The SOP documents have been handed over to the Quality Assurance Center of University XYZ to be formalized.